Suburban Community Settlement in Makassar City (Qualitative Study of Health Education in Efforts to Improve Community Healthy Lifestyle) - Jusmawandi Jusmawandi (Habitus : Jurnal Pendidikan, Sosiologi, dan Antropologi, 2022)
Fisherman's Village, precisely in Untia Village, Biringkanaya District, Makassar City, is one of the villages located on the west side of Makassar City. This village is often a subscriber of news related to unhealthy housing conditions. The role of the Makassar City Government is realized with the slogan "Makassar Tidak Rantasa" is a manifestation of the government's efforts to improve the quality of life of the community. With various stigmas aimed at the village, we are interested in researching health problems related to public education in the fishermen's village. The research method we use is qualitative with a descriptive model and an active participation approach. The results of this study are that people are not too concerned with their environmental conditions, such as throwing garbage anywhere, the condition of the canal is not maintained, clean water is very limited. This condition then gives birth to unhealthy behavior towards children, such as eating with dirty hands, doing activities without wearing sandals and other unhealthy behaviors. this is not considered a problem for them because the concept of health has gone through the process of informal education in the family. So it needs the attention of the Makassar city government in fixing these problems, both in the form of counseling and formal education. AbstrakKampung Nelayan, tepatnya di Kelurahan Untia Kecamatan Biringkanaya Kota Makassar merupakan salah satu perkampungan yang berada di sisi bagian barat kota Makassar. Kampung ini sering menjadi langganan pemberitaan terkait kondisi pemukiman yang tidak sehat. Peran Pemerintah Kota Makassar direalisasikan dengan slogan “Makassar Tidak Rantasa” merupakan wujud upaya pemerintah meningkatkan kualitas hidup masyarakat. Dengan berbagai stigma yang ditujukan ke kampung tersebut, kami tertarik untuk meneliti permasalahan kesehatan yang berkaitan dengan pendidikan masyarakat yang ada di kampung Nelayan. Adapun metode penelitian yang kami gunakan yaitu kualitatif dengan model deksriptif. Adapun hasil dari penelitian ini yaitu masyarakat tidak terlalu mementingkan kondisi lingkungan mereka, seperti membuang sampah sembarang tempat, kondisi kanal yang tidak terurus, air bersih yang sangat terbatas. Kondisi ini kemudian melahirkan perilaku yang tidak sehat, seperti makan dengan tangan kotor, beraktivitas tanpa memakai sandal dan perilaku yang tidak sehat lainnya. hal ini tidak dianggap bukan masalah bagi mereka karena konsep sehat telah melalui proses pendidikan informal dalam keluarga. Sehingga perlu perhatian pemerintah kota Makassar dalam memperbaiki masalah tersebut, baik dalam bentuk penyuluhan maupun pendidikan formal.